OPTIMALISASI TAHAP PRESENTASI MODEL PIMCA PADA PEMBELAJARAN MATRIKS MATERI SPLTV - Vellin F.E Londo; Sylvia J.A. Sumarauw; Vivian E. Regar (CV. ADIBA AISHA AMIRA, 2023)
In the learning process, how to provide material that does not can cause students to get less information about material, lack of understanding of concepts and difficulty solving problems such as training provided, thus causing low learning outcomes. Study on learning the SPLTV material matrix with the Optimization of the Presentation Stage based on MR (Multiple Representation) aims to enable student to obtain material information provided, can master the concept of material, and solve problems such as sample questions and can find out improvement of student learning outcomes. By using the PIMCA model which divided into 4 steps, namely Presentation, Idea Mapping, Conceptualization, Formative Assessment. This research was conducted in the Department of Mathematics with respondents 22 students. From the results of the calculation of the data obtained the average score pretest 6 and the average posttest score 65. Also obtained the average percentage an increase in understanding of the concept of 82,67 as a result there is an increase in understanding the concept so that the Optimization Stage is obtained PIMCA In SPLTV Material Matrix Learning, there is a improvement of learning outcomes and this model can also be an alternative in selection of learning models and can be continued in the STEM field.